DRUG UTILIZATION EVALUATION OF THIRD GENERATION CEPHALOSPORINS IN A TERTIARY CARE HOSPITAL - Krishnamurthy3, Dr.Afzal Khan A.K4, Saugat Dahal1*, Sushobhan Bhandari1, Bhi shma Ghimire1, Dr.N.M Mahesh2, Dr.MS (Journal of Biomedical and Pharmaceutical Research, 2017)
Title: Study on drug utilization evaluation of third generation cephalosporins in tertiary care hospital. Objective: To evaluate prescribing pattern, to identify most common infection treated with third generation cephalosporin and to assess drug related problem. Methodology: A hospital based prospective study was conducted in MVJ medical college and research hospital between the periods for six months after getting consent from the patients. Results: Out of 150 cases collected, the most common prescribed third generation cephalosporins are Ceftriaxone(68%), followed by Cefixime(20.66%) and Cefotaxime(11.33%).In an entire study, the route of administration of parenteral drugs(79.33%) was found more compared to the oral drugs(20.667%).In our study,the drugs per encounter were 5.8 and third generation cephalosporin per prescription was 1.013.Similarly, the most common infections treated with third generation cephalosporins were Lower Respiratory Tract Infection(LRTI)which includes Chronic Obstructive pulmonary Diseases(COPD34.667%), acute bronchitis(12%), chronic bronchitis(10.667%), pneumonia(23.33%), followed by meningitis(9.33%), acute gastritis (7.33%) and others( 2.667%). On culture and sensitivity test, only 12% were found to have done it, majority was done in Blood(33.33%) followed by sputum(22.22%), urine(22.22%), saliva (16.667%) and pleural fluid (5.556%).Regarding drug related problem, two cases(1.33%) were found to have moderate drug-drug interaction between furosemide and ceftriaxone out of total 150cases. Conclusion: Drug use evaluation is an important health issue in an area of medicine. so, health education of the public as well as hospitals and regulation of pharmacies and antibiotic guidelines in hospitals which can help in managing Drug use Evaluation of TGC’S and minimize the risk of future resistance.Keywords: Drug utilization, Cephalosporins